Formulasi Self Nanoemulsifying drug delivery system Enzim Bromelain buah Nanas Ananas comosus - Urva Fresiva; M Fatchur Rochman; Flomaria Tianingsih; Resty Pratiwi; Amalia Anugrahi (Jurnal Farmasi & Sains Indonesia, 2025)
The pineapple fruit's bromelain enzyme exhibits pharmacological activity as an antibacterial and anti-inflammatory. The bromelain enzyme was formulated as tablets and powders in earlier research, although this still had the disadvantage of having a higher formulation resistance. Formulating and characterizing SNEDDS of the bromelain enzyme with oil phase, surfactant, and co-surfactant—specifically, clove oil, propylene glycol, and PEG 400—is the goal of this study. The process for creating SNEDDS bromelain enzyme involves combining the carrier in different quantities, adding the enzyme, and evaluating it based on factors including homogeneity, adhesion, spreadability, clarity, and organoleptic characteristics. The active ingredient in the SNEDDS formulation that was obtained was 360 mg of bromelain enzyme per milliliter of SNEDDS. With a 2:5:3 concentration ratio of clove oil, PG, and PEG 400, the transmittance percentage of SNEDDS is 98.54 ± 0.02%, the spreadability is 2.2 cm, the adhesion is 116 seconds, and the pH is 6.48. In comparison to other carrier concentrations, SNEDDS bromelain enzyme SNEDDS with a concentration ratio of 2:5:3 for clove oil, PG, and PEG 400 yields superior characteristic results.